Vibration and power flow analysis of periodically reinforced plates - Xu, H. A.; Li, W. L. (Science China Technological Sciences, 2011)
In this paper an analytical method is proposed to investigate the vibration and power flows of periodically reinforced plate with general boundary conditions. Both the plate and stiffening beams are modeled as 3D structural components, and the couplings at the interfaces are specified in terms of 3D elastic joints. The displacement function for each stiffening beam is expressed as a modified Fourier cosine series, and the transverse and in-plane displacements for the plate are similarly expressed as the 2D versions of the modified Fourier cosine series expansions. The unknown Fourier coefficients are calculated using the Rayleigh-Ritz technique. The key advantages of the proposed method include： 1） it is capable of dealing with arbitrary boundary and coupling conditions, 2） it allows modeling any number of reinforcing beams with arbitrary lengths, and 3） the structural intensity, power flows, and kinetic energy distributions are readily calculated analytically from the displacement functions through appropriate mathematical （differential） operations, to name a few. The power flow characteristics of periodically reinforced plates are studied against various influencing factors, such as, plate and beam boundary conditions, coupling conditions, excitation locations, and dislocations resulting from minor misplacement of a reinforcing beam.